1977
DOI: 10.1007/bf01257018
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of catecholamine release by alpha-adrenergic activation: Interaction with Na, K-ATPase

Abstract: In rat adrenal gland incubated in vitro, phenylephrine and naphazoline inhibited the release of catecholamines (CA) induced in a medium containing K+ (5.6mM). In K+-free medium or in the presence of ouabain (10(-3) M) phenylephrine and naphazoline had no effect on CA release. The alpha-adrenergic blockers, phentolamine and phenoxybenzamine, increased CA release in a K+-medium but had no effect on CA release from adrenal medulla in a K+-free or ouabain (10(-3) M) containing medium. PGE2 inhibited the release of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…The present paper confirms and extends our previous finding on activation of adrenal medullary Na,K-ATPase by ax-adrenoceptor agonists (Gutman & Boonyaviroj, 1977a). Enhancement of brain Na,K-ATPase activity by adrenoceptor agonists has been described by several authors (Yoshimura, 1973;Godfraind, Koch & Verbeke, 1974;Lee & Phillis, 1977).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present paper confirms and extends our previous finding on activation of adrenal medullary Na,K-ATPase by ax-adrenoceptor agonists (Gutman & Boonyaviroj, 1977a). Enhancement of brain Na,K-ATPase activity by adrenoceptor agonists has been described by several authors (Yoshimura, 1973;Godfraind, Koch & Verbeke, 1974;Lee & Phillis, 1977).…”
Section: Discussionsupporting
confidence: 93%
“…This finding indicated the possibility that the action of a-agonists involved activation of the sodium pump (Na,K-ATPase) (Gutman & Boonyaviroj, 1977a;Gutman, 1978). This possibility was corroborated by the finding that activation of the sodium 0007-1188/80/130135-08 $01.00 pump by different means suppressed CA secretion from the adrenal medulla (Gutman & Boonyaviroj, 1977b).…”
Section: Introductionsupporting
confidence: 72%
“…In experimental studies, pseudoephedrine and ephedrine are potent stimulants of the Na + -K + -ATPase activity [18]. Intentional ingestion of large amounts of pseudoephedrine and the abuse of ephedrine used in some cough mixture can cause severe hypokalaemia [19].…”
Section: Decongestantsmentioning
confidence: 99%
“…Indeed, a recent study performed using rat chromaffin cells has demonstrated an autocrine negative modulation of -type Ca 2+ channels via adrenergic receptors, representing a possible mechanism regulating Ca 2+ -dependent exocytosis through voltage-gated channels (Hernandez-Guijo et al 1999). Moreover, other studies have demonstrated an inhibitory adrenergic regulation of Na + influx, thereby affecting the extent of cell depolarization and catecholamine release (Gutman & Boonyaviroj 1977, Wada et al 1985. Because -type channels (Ca 2+ voltage-gated channels) contribute over 50% of the total Ca 2+ current, these mechanisms may form the basis of the adrenergic autocrine/paracrine control of catecholamine secretion.…”
Section: Adrenergic Regulation Of Non-cholinergic Secretagoguesmentioning
confidence: 99%
“…For example, it has been reported frequently that -adrenoceptor agonists and antagonists exert powerful influences on stimulus-evoked release of noradrenaline from nerve terminals (Starke et al 1974b, Langer et al 1977, Nilsson 1983. Although controversial, similar interactions have been described in mammalian chromaffin cells leading investigators to suggest an autocrine/paracrine regulation of catecholamine release via activation of chromaffin cell adrenergic receptors (Gutman & Boonyaviroj 1977, Boonyaviroj et al 1979, Cohen et al 1980, Greenberg & Zinder 1982, Wada et al 1982, Powis & Baker 1985, Sharma et al 1986, Orts et al 1987.…”
Section: Introductionmentioning
confidence: 99%